Implementation of Mudharabah Contract On Sharia Bank Financing Products In Indonesia - Ahmad Kamil Ihsani; Asyari Hasan (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
This study investigates how Indonesian Islamic Banks implement mudharabah contracts on financing product. This study uses descriptive research, namely research that defines facts, data, and information gathered from published studies such as books and journals to research findings relevant to the research topic. According to this study, the development of Islamic banks in Indonesia has seen positive growth. One of the products offered by Islamic banks is financing products. This financing is accomplished through the use of various contracts, one of which is the mudharabah contract, which employs a profit-sharing system. This profit-sharing system will be devoted to customers who apply for financing from Islamic Banks that are used to run businesses owned by customers. In the process, the bank will carry out several stages and procedures such as verification to determine the provision of such financing to customers. If it has been verified, the Bank will provide funds or capital to the client to be managed. The customer’s results or profits will be divided between both the customer and the bank under the terms of mudharabah contract. In the process of implementation, this mudharabah contract is based on Islamic law such as the Qur'an and al-Hadith as well as legislation such as MUI fatwas, PSAK as well as OJK, and Bank Indonesia policies.